CHARACTERIZATION OF TEMPORAL RAINFALL DISTRIBUTION IN FLORIANÓPOLIS, SANTA CATARINA, BRAZIL - Back, Alvaro José; Rodrigues, Maria Laura Guimarães (Revista Brasileira de Climatologia, 2021)
Temporal rainfall distribution is an important information for the preparation of the design hyetograph, directly influencing peak flow. This study analyzes the temporal rainfall distribution of Florianópolis city. We used rainfall data from 1986 to 2012 obtained from the Brazilian National Meteorological Institute (INMET). Heavy rainfall events were classified and individualized, and intensities were determined at each 5% interval of the duration. Rainfall was classified in Huff quartiles and identified by season and duration. Rainfall accumulation curves in the 10-90 percentiles were determined as well as 50% probability curves for each season and duration. The results showed that type I rainfall is the most frequent and that summer rains have a more anticipated pattern. Important differences were found between rainfall durations. The advance coefficient varies with rainfall duration, and averaged 0.389.